EVOLUTION OF FACTORS AFFECTING PSYCHOLOGICAL WELL-BEING IN THE MUNICIPAL WORK ENVIRONMENT - Jonāne, Lolita; Stafecka, Irēna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Employees’ wellbeing and health are very broad concepts, but different kinds of stressors are influencing them. The aim of this research is to identify the risk factors in the municipal work environment of Latgale region and to find solutions for risk reduction. The need for such research is justified by recent research in various countries, which shows that the psychosocial problems adversely affect wellbeing, productivity and health. In addition, forthcoming administrative-territorial reform in 2021 may intensify tensions. 123 employees were surveyed and surveys data were analyzed. It has been found that tension at work is caused by uncertainty about the future career prospects, overload and competition. Sometimes there is a lack of emotional intelligence, insufficient effective communication skills with colleagues and clients, and reassessment of one's affective abilities.